(untitled) (LACCEI, 2024)
In the present investigation, the main objective was to implement lean manufacturing to improve the performance of the dispatch process and as specific objectives, it was to carry out a diagnosis of the performance of the dispatch process, to elaborate a diagnosis to determine the causes that reduce the performance of the dispatch process. dispatch, implement lean manufacturing, determine the performance of the dispatch process after implementation and perform economic analysis. This research was applied with a pre-experimental design. Tools such as VSM, SMED, 5’S and synchronization with suppliers and Ishikawa and Pareto diagram were applied for the development. 1324 containers from the 2021 campaign were sampled. The implementation of SMED reduced the cycle time to 74.34 minutes, the 5’S increased compliance by 92%, VSM reduced the process to 4 stages and supplier synchronization managed to increase by 82% . Deviation in delivery time was reduced to 0.35% and on-time delivery increased to 97%. The economic analysis of the implementation is viable with an IR of 1.17.